Banking Contribution in Strengthening Food Security Through 7P Marketing Strategy: Study on BSI KC Surabaya Jemur Handayani - Sholiha, Innatu; Rahmawati, Lilik (Indonesian Journal for Entrepreneurial Review, 2025)
The presence of gold installment products at other Islamic banks and non-bank Islamic financial institutions such as Islamic pawnshops has created quite tight competition. This study aims to examine how the marketing strategy implemented by BSI KC Surabaya Jemur Handayani can maintain the position currently obtained and can increase one of its incomes from gold installment products. The research method used is qualitative descriptive. Data collection techniques using observation, interviews and documentation. Based on the results of the study, it shows that Bank Syariah Indonesia KC Surabaya Jemur Handayani has implemented a 7P marketing mix. In terms of product, the bank has emphasized product quality. Pricing for gold installment products is set according to market prices that can compete with other financial institutions. In terms of location, the bank occupies a strategic location so that it is easily accessible and accessible by customers. The marketing strategy for the promotion aspect of gold installment products is applied to various online and offline media. In terms of people, the bank provides the best service to its customers. The process aspect of the overall gold installment product marketing strategy has been good. Finally, the marketing strategy for the physical evidence aspect is carried out by the bank by designing an office that supports comfort for its employees and customers. In addition, effective marketing strategies have a positive impact on the economic welfare of customers, will have an impact on food security and increase national economic stability.